L’expérience d’étudiants universitaires ayant agi comme pairs aidants dans le cadre du programme Korsa - Grégoire, Simon; Saules, Gaëlle; Cyr, Emma; Lachance, Lise (Canadian Journal of Education/Revue canadienne de l'éducation, 2024)
In recent years, peer support programs have been introduced in post-secondary institutions to promote wellness and reduce psychological distress among students. Although studies have been conducted to assess the impact of these programs on peers, few have been led to explore the experience of students working as peer supporters. In this study, a focus group and semi-structured interviews were conducted to investigate the experience of eleven university students who acted as peer supporters in a peer support program offered at three universities in Montreal. The results of this study provide a better understanding of what motivated the peer supporters to undertake this program, their concerns, their experience, what they appreciated and found challenging, and the impact the program had on them. It also offers some recommendations for implementing a peer support program in post-secondary settings.